2014
DOI: 10.1007/s00204-014-1408-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficit in learning and memory of rats with chronic fluorosis correlates with the decreased expressions of M1 and M3 muscarinic acetylcholine receptors

Abstract: To reveal the molecular mechanism of deficit in learning and memory induced by chronic fluorosis, the expression of muscarinic acetylcholine receptors (mAChRs) and oxidative stress were investigated. Sixty Sprague-Dawley (SD) rats were divided randomly into two groups (30 cases in each), i.e., the control group (<0.5 ppm fluoride in drinking water) and the fluoride group (50 ppm fluoride) for 10 months of treatment. The pups born from SD mothers with or without chronic fluorosis were selected at postnatal days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Therefore, the doses of fluoride exposed to mice were equivalent to 1.5 ppm (close to the drinking water standard set by WHO) and 15 ppm, respectively, in drinking water for humans. In previous studies by our group, we observed that the rats with chronic fluorosis exhibited a significantly declined ability of learning and memory [24,25]. In the behavioral test, both the WT and APP/PS1 double-transgenic mice exposed to a high level of fluoride performed more poorly than the controls, indicating that impairment of spatial learning and memory.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Therefore, the doses of fluoride exposed to mice were equivalent to 1.5 ppm (close to the drinking water standard set by WHO) and 15 ppm, respectively, in drinking water for humans. In previous studies by our group, we observed that the rats with chronic fluorosis exhibited a significantly declined ability of learning and memory [24,25]. In the behavioral test, both the WT and APP/PS1 double-transgenic mice exposed to a high level of fluoride performed more poorly than the controls, indicating that impairment of spatial learning and memory.…”
Section: Discussionmentioning
confidence: 79%
“…Oxidative stress is often defined as an imbalance between free radical formation and their removal by cellular anti-oxidative systems, which leads to accumulation of toxic oxy-radicals, a process that plays a key role in both fluorosis and AD [55][56][57][58]. In recent years, it has been recognized that higher concentrations of fluoride result in neuronal dysfunction by elevating levels of free radicals while reducing the activities of antioxidant enzymes and contents of antioxidant compounds [24,25]. Oxidative stress damages all classes of organic molecules in the cells, causing excessive lipid peroxidation and protein oxidation in the brains of patient with AD [59,60].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 In brief, 200 ml of the supernatant prepared as described above were placed into a micro-centrifuge tube and 600 ml of the TBARS solution then added. This mixture was incubated at 95 C for 60 min and cooled to room temperature in an ice bath for 10 min.…”
Section: à44ctmentioning
confidence: 99%